Strengthening the scientific basis of in situ conservation of agricultural biodiversity on-farm. Options for data collecting and analysis: Proceedings of a workshop to develop tools and procedures for in situ conservation on-farm, 25-29 August 1997, Rome, Italy - Jarvis, Devra I.; Hodgkin, T.; International Plant Genetic Resources Institute (1998)
In August, 1997, IPGRI, organized a workshop on how to develop tools and procedures of data collections and analyses for its ongoing global in situ conservation programme in the nine partner countries. In the workshop scientists, project leaders and researchers of various disciplines from the nine partner countries, FAO, Universities, NGOs, and donor organizations got together and exchanged their experiences of field data collections and analyses for the sustainable utilization and conservation of PGR on-farm. This proceedings is the outcome of the workshop intended to help partners collect and analyze socioeconomic, cultural, environmental, genetic and biological data for in situ conservation and to add value to traditional varieties. Another objective was to forge mutual partnership between scientists and farmers through participatory plant breeding (PPB).